Old brown bread’s nutritional usability in broiler feeds - Krička, Tajana (Array, 2020)
The most important aspect of broiler production is feeding, whose costs represent about 70% of total costs. Thus, the growth of poultry production has been based on a strong consumer demand for products that are cheap, safe, and healthy. That kind of product is old bread, whose return from the store represent a problem for its remediation. For the use of the old bread as a feed, the European Union has promulgated a series of regulations and directives, which order a ban on its utilization without prior treatment. The most common treatments are pelleting and extrusion. In poultry, the upper limit for the use of the old bread in feedstuff is often prescribed and amounts to 15%. The aim of this paper was to determine a possibility to use 5 and 10% old brown pelleted bread in feed mixtures for broilers fattening. The study has shown that the addition of old bread significantly improves broiler production indicators. The best results and a more favorable ratio of omega 6 and omega 3 fatty acids in the chicken muscles were obtained in the group fed with a 10‐percent share of old brown bread (p<0.05). Such a processed old bread can be used as a new ingredient in animal feed production as a partial replacement for maize component.